2021
DOI: 10.46642/efd.v26i277.2832
|View full text |Cite
|
Sign up to set email alerts
|

Educação Física na escola: o ensino e aprendizagem em tempos de pandemia

Abstract: O presente estudo teve como objetivo analisar os avanços, desafios e limitações do ensino e aprendizagem da Educação Física no ensino remoto, nas escolas públicas estaduais paranaenses, perante o contexto da pandemia da COVID-19. A pesquisa foi realizada nas escolas do Núcleo Regional de Educação de Guarapuava, participaram 33 professores de Educação Física respondentes do questionário no formato Google forms. Os dados da pesquisa foram organizados em categorias, nas quais apresentamos elementos da prática ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Finally, four articles were considered suitable for analysis and inclusion in this integrative review, as shown in Table 1: Four surveys were found, two from the CAPES journal portal, one from SCIELO and one from LILACS. The research selected for analysis is field research, one with a quantitative approach (MARTINS et al, 2022) and the other three qualitative (GODOI et al, 2020;MADRID et al, 2021 andCONCEICÃO 2021), as shows table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, four articles were considered suitable for analysis and inclusion in this integrative review, as shown in Table 1: Four surveys were found, two from the CAPES journal portal, one from SCIELO and one from LILACS. The research selected for analysis is field research, one with a quantitative approach (MARTINS et al, 2022) and the other three qualitative (GODOI et al, 2020;MADRID et al, 2021 andCONCEICÃO 2021), as shows table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Ainda mais em situação de pandemia que as escolas vêm enfrentando no ano de 2020 a 2021, ocorrida pelo novo coronavírus. A maioria dos professores compreendem que os desafios foram muitos, os quais implicaram em dificuldades que limitaram o ensino e aprendizagem nas aulas de educação física (Madrid et al, 2021).…”
Section: Discussionunclassified
“…Sobre todo, por el poco dominio de la tecnología y los resultados inesperados que podría tener la educación a distancia (Hortigüela-Alcalá et al, 2021). Estos resultados se asocian a los de otras investigaciones en EF en el contexto de pandemia, donde el profesorado reconoce dificultades por la poca preparación en torno a las competencias digitales (Machado, Fonseca, Medeiros & Fernandes, 2020;Madrid, Taques, Honorato & Grando, 2021). Es comprensible que los resultados de investigaciones en torno a las emociones en EF en el contexto de la pandemia se enfoquen en el aspecto más estresante y asociado a las emociones negativas para el BS.…”
Section: Discussionunclassified